2019
DOI: 10.3390/brainsci9070157
|View full text |Cite
|
Sign up to set email alerts
|

Poor Synchronization to Musical Beat Generalizes to Speech

Abstract: The rhythmic nature of speech may recruit entrainment mechanisms in a manner similar to music. In the current study, we tested the hypothesis that individuals who display a severe deficit in synchronizing their taps to a musical beat (called beat-deaf here) would also experience difficulties entraining to speech. The beat-deaf participants and their matched controls were required to align taps with the perceived regularity in the rhythm of naturally spoken, regularly spoken, and sung sentences. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 119 publications
(171 reference statements)
1
27
0
Order By: Relevance
“…What differs is the regularity of their tapping. Irregularity in spontaneous tapping was not expected, as it has not been reported previously 2,4,12 except in our own recent work 24 . The reason might come from the fact that our study includes one of the largest samples of individuals with a beat-finding disorder and collected over twice as many tapping data.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…What differs is the regularity of their tapping. Irregularity in spontaneous tapping was not expected, as it has not been reported previously 2,4,12 except in our own recent work 24 . The reason might come from the fact that our study includes one of the largest samples of individuals with a beat-finding disorder and collected over twice as many tapping data.…”
Section: Discussionsupporting
confidence: 53%
“…Together with the breakdown of synchronization with very fast tempi (225 ms between tones) and poor error-correction at moderately fast tempi (337 ms between tones), our results suggest that the hallmark of the impaired intrinsic rhythmicity of beat-impaired individuals lies in an alteration of the fine-tuning that characterizes typical human adults' tapping. The deficit is not specific to music but extends to other auditory rhythms, provided by a metronome as here, or in speech and song as in 24 . Thus, the results point to the presence of a basic deficiency in timekeeping mechanisms that affect entrainment in general.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The rhythmic patterning of both speech and music has been proposed to draw on domain-general abilities which are required to perceive and process temporal features of sound [22,23]. Accordingly, three studies present data in line with common rhythm processing resources in M&L. First, Lagrois et al [6] found that individuals with beat finding deficits in music-so called "beat-deaf" individuals-also show deficits in synchronizing their taps with speech rhythm, and more generally, in regular tapping without external rhythms. The authors argue that this pattern of deficits may arise from a basic deficiency in timekeeping mechanisms that affect rhythm perception across domains.…”
mentioning
confidence: 98%
“…As argued in the review article of Reybrouck and Podlipniak [9], some of these sound features and their common preconceptual affective meanings may even reflect joint evolutionary roots of M&L that still prevail today, for example, in musical expressivity and speech prosody. Notably, a feature that was particularly central to half of all contributions is the temporal structure of M&L, i.e., the patterning of strong and weak syllables or beats that make up rhythm, meter and prosodic stress [6][7][8][10][11][12][13]15].…”
mentioning
confidence: 99%